Towards SKA studies of the fast radio transient Universe - Hall, P; Colegate, Timothy; Macquart, Jean-pierre; Clarke, Nathan; Tingay, Steven; Wayth, R; Trott, Cathryn (Proceedings of Science, 2012)
The SKA is likely to produce transformational insights into the fast transient Universe. So little is currently known about this observational window that much of the SKA time domain science program has been lumped into the "exploration of the unknown" theme. Unsurprisingly, no clarity has hitherto emerged on the associated operational or architectural requirements. However, with the recent advent of highly-capable Pathfinders and new programs targeted at exploring key system design questions, insights into these and other critical issues are emerging. Newly-optimized signal combination strategies for large-N arrays, cost effective hardware processing methods, and improved signal detection and localization algorithms are all being refined and implemented on test platforms. Somewhat unexpectedly, the power of SKA-low as a fast transients instrument has recently become evident. This paper reviews a new detection-rate metric developed at ICRAR/Curtin, summarizes the present state of transients surveys, predicts SKA performance, and outlines important messages for the SKA project - particularly the SKA1 system design now underway.